Synthesis, functionalization and characterization of UV-curable lactic acid based oligomers to be used as surgical adhesives - Santos, João (2018)
The synthesis, functionalization and characterization of low molecular weight L-lactic acid based oligomers to be used as new UV-curable bioadhesives are presented herein. Prepolymers hydroxyl terminated were produced by L-lactic acid dehydration with 1,4-butanediol. The prepolymer was further modified with photoreactive sites by adding an isocyanate-functional unsaturated acrylic ester, which was used for the first time in the biomedical field (LAROMER® LR 9000). Films were afterwards produced upon UV irradiation for 120 s, using a biocompatible photoinitiator (Irgacure® 2959), and finally characterized. The synthesized films exhibited a moderate swelling ratio, suitable for the envisioned application. DSC analysis confirmed an increase in Tg values after each synthesis step. Nevertheless, the film Tg remains lower than the physiological and room temperature. TGA confirmed an improved stability of films at high temperatures. The in vitro degradation tests showed their susceptibility to hydrolysis at 37 °C, suitable for short-term uses. Preliminary evaluation of the adhesion capacity suggested that the synthesized material may be effective in sustaining wound closure and repair. The surface energy was also measured and its value was lower than the ones from blood or skin which supports the previous statement. Blood compatibility studies, cell viability assays (using human dermal fibroblasts) and bacterial inhibition tests (using two bacteria models) were performed. The results indicated that cured adhesive is bio/haemocompatible and possesses antimicrobial activity. Altogether, characterization results showed that the produced material presented a set of properties suitable for biomedical applications, particularly as a surgical adhesive.